Estudo da reforma a vapor do glicerol: análise termodinâmica e avaliação de catalisadores Pt-Ru suportados em carbono - Figueira, Camila Emilia (2010)
The continuous decreasing of fuel fossil sources has been accelerating the seek for alternative energetic sources. The difficulty in consuming all glycerol produced, which is three times bigger than the demand, is the main concern around the biofuels process production. Given that this glycerol has different characteristics from the well consumed glycerol in the pharm business, such as color and impurities. Besides, there is a lack of defined standards in Brazil in the sense of how to dispose such product. However, alternative uses for glycerol (by-product from the biofuels production) will confirm the feasibility of the biodiesel process, particularly if we take into account its decentralized production. The glycerol steam reforming can yield up to 4 moles of H2 and 3 moles of CO per consumed mole of glycerol. In this work, the catalytic tests were performed with monometallic and bimetallic ruthenium and platinum catalyst in a tubular reactor with 30% wt of glycerol in the feed, using 6 and 20 pressures conditions. It was also carried out tests with 100 hours of reaction in order to verify its activity and stability. Along with the catalyst studies, the effects of temperature, feed flow and ruthenium particle size under monometallic and bimetallic catalyst were analyzed. Besides, it was also evaluated the reaction thermodynamics of glycerol steam reforming due to temperature, pressure and mass composition of glycerol over the production profiles of the most valuable products in the chemical equilibrium. Therefore, the objective of this work is to present the study of glycerol steam reforming employing different catalysts and under different operational conditions and evaluating its performances in the production of chemical products with high commercial value.